The Britain guide. (UK : BTA, 1995)
The country, London, entertainment and nightlife, learning English in Britain, England, Scotland, Wales, travelling around Britain, Information for travellers.
Keywords: Geography; Great Britain; Great Britain -- Geography; Great Britain -- Geography